Islamic Education in The Era of Globalization - Soleha, Maratus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Islamic education plays a crucial role in nurturing competent, knowledgeable, devout, and altruistic individuals within the family setting. The aim of this study is to explore the dynamics of Islamic education in the context of globalization. Employing a literature review research method, this article delves into the manifold impacts of globalization on Muslims, presenting both positive and negative facets. Furthermore, it addresses the challenges that globalization poses to Islamic education, emphasizing the imperative to mitigate adverse effects and prevent the potential depletion of a generation ill-prepared to confront global challenges. Key challenges faced by Islamic education in the era of globalization include inadequate teaching resources, low educator welfare, a predominantly cognitive learning orientation, suboptimal madrasah management, moral crises, and lingering societal biases against madrasahs. To counter these challenges, strategic measures must be adopted, such as establishing a robust Islamic education paradigm and implementing effective educational practices while enhancing teacher quality.